Effect of growing location, malaxation duration and citric acid treatment on the quality of olive oil - Chih, Hui Jun; James, Anthony; Jayasena, Vijay; Dhaliwal, Satvinder (John Wiley and Sons Inc., 2013)
BACKGROUND: The total phenolic compounds of olive oil exert antiradical activity at cellular level and can prevent cardiovascular disease, metabolic syndrome and cancer. Increased awareness of its health benefits has increased the consumption of olive oil around the world. An alternative processing technique effective in increasing the amount of oil extracted while maintaining the oil quality is needed to meet the rising global demand for olive oil. RESULTS: Addition of 0.3 g mL−1 citric acid at 1:1000 (v/w) to olive paste followed by a 30 min malaxation period significantly increased the oil recovery, concentration of total phenolic compounds and antiradical activity by 46.23, 120.27 and 31.48% respectively. While there was no significant effect on the acidity, the peroxide value was significantly reduced by 63.85%. The organoleptic characteristics of the olive oil extracted with citric acid were also comparable to those of the control. CONCLUSION: Addition of 0.3 g mL−1 citric acid (i.e. 30% w/v) at 1:1000 (v/w) to olive paste followed by a 30 min malaxation period in a Blixer® 4.0 blender is the most promising extraction technique to improve the oil recovery, concentration of total phenolic compounds and antiradical activity of the extracted olive oil without compromising other quality parameters.